Lead Users and Early Adopters on the Web: The Role of New Technology Product Blogs - Droge, Cornelia; Stanko, Michael A.; Pollitte, Wesley A. (The Journal of product innovation management, 2010)
Lead users and early adopters are often blogging or reading and commenting on blogs. Blogs, which are characterized by postings, links, and readers' comments, create a virtual “community” of blogger and readers. Members self‐select, and then the community gels around a theme or idea, product, industry, hobby, or any other subject. While community creation is one chief function of blogs, the information‐sharing, entertainment, or self‐ or value‐expressive functions are also important. Thus, new product development (NPD) managers can glean a great deal of information about what these audiences are thinking. The significance of blogging to NPD managers also lies in the shift of focus from being separate from to being immersed in these communities. Immersion enhances the potential of close relationships, sharing experiences, and co‐creating value with blogging communities through innovation. The focus of the study is on the roles of blogs in new product development, and an exploratory content analysis of new technology product blog postings is described. The goal was to examine what blogs actually say (and don't say) and to classify content based on the core elements of the marketing mix: product (including attributes and service aspects); price (including price comparisons); channel; and promotion. The bulk of the content was in the product category: for example, features (mentioned by 87.14%); overall evaluations (52.86%); performance (28.57%); compatibility (27.14%); ease of use (20%); and style (17.14%). About half discussed price, and about half discussed some channel aspect. The content is analyzed in detail, and implications for NPD mangers are discussed. People voluntarily join new product blogging communities, and if the manager of that product is not “present” (at least as an observer of this “straw poll”) an entire new product marketing agenda can be set by the community. Implicitly or explicitly, blogs can position the value proposition of the product in a prime target audience's mind. Such positioning could be advantageous or catastrophic as far as the NPD manager is concerned.